Investigation of Pseudo-Ricci Symmetric Spacetimes in Gray’s Subspaces - Sameh Shenawy; Uday Chand De; Nasser Bin Turki; Suliman Alsaeed; Abdallah Abdelhameed Syied (Journal of Mathematics)
In the present paper, we focused our attention to study pseudo-Ricci symmetric spacetimes in Gray’s decomposition subspaces. It is proved that PRSn spacetimes are Ricci flat in trivial, A, and B subspaces, whereas perfect fluid in subspaces I, I⊕A, and I⊕B, and have zero scalar curvature in subspace A⊕B. Finally, it is proved that pseudo-Ricci symmetric GRW spacetimes are vacuum, and as a consequence of this result, we address several corollaries.